Comprehensive rehabilitation and job reintegration of people with severe mental illness in a Latin American country: REINTEGRA study protocol - Jaime Carmona-Huerta; Sol Durand-Arias; Elsy Cárdenas-García; J. Carlos Arámbula-Román; Marianne Guzmán-Ramírez; Isabel Estrada-Ramírez; María Trinidad Amezcua-Ramírez; Verónica Lastra-González; Santiago Castiello-de Obeso; Alejandro Aldana-López (BMC Psychiatry, 2023)
Abstract Background Despite the increasing use of comprehensive rehabilitation models for people with severe mental illness (SMI), there are still limitations to their implementation and replicability in a consensual way, particularly in Latin American countries. The REINTEGRA program aims to be a standardized model of comprehensive rehabilitation focused on psychosocial and cognitive improvement through a set of interventions on different areas of people’s functionality, with the goal of reintegrating people with SMI into the labour market. In this paper we summarize the protocol for its subsequent implementation in a mental health institution in Mexico. Method The protocol is based on a quasi-experimental, prospective longitudinal study, with a pragmatic or naturalistic control group. It will be carried out in three phases. Phase 1 consists of a series of interventions focused on psychosocial improvement; Phase 2 focuses on cognitive and behavioral improvement treatments; and Phase 3 targets psychosocial recovery through rehabilitation and reintegration into the labour market. The overall procedure will be monitored with standarized evaluations at different stages of the program. Discussion This study presents a model of integral rehabilitation of people with SMI. At the moment, one of the obstacles to overcome is the organization and procedural control of the different actors needed for its implementation (nurses, psychologists, doctors, companies, institutions, etc.). REINTEGRA will be the first comprehensive rehabilitation model that includes systematized procedures for job reinsertion for people with SMI in Mexico, which aims to be a standardized tool of easy adaptation and the replicability for other mental health centers and institutions.